2014
DOI: 10.1161/hypertensionaha.114.03718
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Resistant Hypertension in a Large Health Maintenance Organization in Israel

Abstract: A rterial hypertension is associated with an increased risk of cardiovascular morbidity and mortality.1,2 Blood pressure (BP) reduction has been shown to reduce fatal and nonfatal outcomes in hypertensive patients. 3,4 Despite the improvement in diagnostic options and therapeutic interventions, observational studies continue to show persistently low rates of BP control in the general population of hypertensive patients. 5,6 In some of these patients, hypertension is resistant to treatment and persists despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 27 publications
4
75
2
Order By: Relevance
“…Besides, a study conducted in Japan showed that increasing age is significantly associated with RH (P < 0.05) [19]. A study conducted in the Middle East, including 65,710 hypertensive patients, reported that elderly people were more able to have RH with a significant P-value of < 0.05 [24]. Obesity is another important significant finding, which has a strongly positive association with RH.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, a study conducted in Japan showed that increasing age is significantly associated with RH (P < 0.05) [19]. A study conducted in the Middle East, including 65,710 hypertensive patients, reported that elderly people were more able to have RH with a significant P-value of < 0.05 [24]. Obesity is another important significant finding, which has a strongly positive association with RH.…”
Section: Discussionmentioning
confidence: 96%
“…45 When resistant hypertension is more rigorously defined as office BP consistently >140/90 mmHg and home or daytime ambulatory BP consistently >135/85 mmHg despite treatment with three or more of the five state-of-theart antihypertensive agents (calcium-channel blockers, angiotensin-converting-enzyme inhibitors, angiotensinreceptor blockers, potent thiazide-type diuretics, and vasodilating β-blocker), the prevalence might be as low as 2% of the hypertensive population. 43 Despite this much more conservative estimate, this prevalence still equates to 1.5-2.0 million people in the USA. In other words, 'truly resistant hypertension' is not an all-or-none designation and should be more accurately termed 'difficult primary hypertension' .…”
Section: Drug-resistant Hypertensionmentioning
confidence: 99%
“…However, this subset also includes an unknown proportion of patients with secondary and white coat hypertension and poorly adherent patients. In the 2010-2011 database of a large Israeli healthcare organisation [34 ], resistant hypertensive patients defined as uncontrolled patients despite adherence to a drug regimen including a diuretic and at least 2 other antihypertensive drug classes at their maximal recommended dose accounted for only 2.2% of uncontrolled hypertensive patients and <1% of the total study population. This proportion may still be an overestimate, as screening for secondary or white coat resistant hypertension was performed only in a small minority of patients [34 ].…”
Section: Symplicity Htn-3 Aftermathmentioning
confidence: 99%
“…In the 2010-2011 database of a large Israeli healthcare organisation [34 ], resistant hypertensive patients defined as uncontrolled patients despite adherence to a drug regimen including a diuretic and at least 2 other antihypertensive drug classes at their maximal recommended dose accounted for only 2.2% of uncontrolled hypertensive patients and <1% of the total study population. This proportion may still be an overestimate, as screening for secondary or white coat resistant hypertension was performed only in a small minority of patients [34 ]. Along the same lines, in a single centre retrospective chart review, the proportion of patients with resistant hypertension decreased from 30.9% to 3.4% when triple therapy had to include maximally dosed medications including a diuretic [35 ].…”
Section: Symplicity Htn-3 Aftermathmentioning
confidence: 99%